Stubborn Entanglements - Wheeler, Rachel M. (Church history, 2024)
Kathryn Gin Lum's Heathen is so rich and so vast, I struggled to know where to begin! As I read, I kept being prompted to think back to sources I had encountered in my own research over the years and to think about them in new ways. And so, rather than trying to summarize the book's arguments, I'll aim to preview some of Gin Lum's central interventions by running various bits of sources from my research through the filter of Heathen. My hope is that this process conveys what I see as the broad reach and significance of Heathen, while also raising a few points for further consideration. I have tried to align my research tidbits with particular threads and claims Gin Lum presents.